Long-term care reform and the labor supply of household members: Evidence from a quasi-experiment - Johannes Geyer; Thorben Korfhage (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
Germany introduced a new mandatory insurance for long-term care in 1995 as part of its social security system. It replaced a system based on means tested social welfare. Benefits from the long-term care insurance are not means tested and depend on the required level of care. The insurance provides both benefits in kind and cash benefits. The new scheme improved the situation for households to organize informal care at home. This was one goal of the reform since policymakers view informal care as a cost-saving alternative to formal care. This view however neglects possible opportunity costs of reduced labor supply of carers. We exploit this reform as a quasi-experiment and examine its effect on the labor supply of caregivers who live in the same household as the care recipient. We find strong negative labor market effects for men but not for women. We conduct a series of robustness tests and find results to be stable. – – Im Jahr 1995 wurde in Deutschland eine neue Pflegeversicherung eingeführt. Als Pflichtversicherung ist sie eine eigenständige Säule der Sozialversicherung und ersetzte ein System der einkommensabhängigen Sozialhilfe. Leistungen der neuen Pflegeversicherung werden durch den Grad der Pflegebedürftigkeit bestimmt und sind einkommensunabhängig. Da anspruchsberechtigte Pflegebedürftige zwischen Geld- und Sachleistungen wählen können, wurde die Situation von Haushalten, die häusliche, informelle Pflege organisieren müssen verbessert. Die informelle Pflege zu stärken war eines der wichtigsten Ziele der Pflegereform, da sie häufig als die kostengünstige Alternative im Vergleich zu formellen Pflege wahrgenommen wird. Diese Sichtweise ignoriert jedoch Opportunitätskosten, die entstehen, wenn Pflegende ihr Arbeitsangebot reduzieren, um die Doppelbelastung aus Pflege und Lohnarbeit abzuschwächen. Wir nutzen die Reform als Quasi-Experiment und untersuchen ihren Einfluss auf das Arbeitsangebot von Pflegenden, die mit einer pflegebedürftigen Person in einem Haushalt wohnen. Wir finden starke negative Arbeitsangebotseffekte für Männer, jedoch keine Effekte für Frauen.
Keywords: J22; H31; I13; 330; labor supply; long-term care; long-term care insurance; natural experiment; quasi-experiment